Hardware implementation of Reed-Solomon error correction technique for wireless sensor network based on error pattern analysis - Tan P.-L.; Cheah C.-L.; Ho C.-K. (Institute of Electrical and Electronics Engineers Inc., 2023)
In this paper, we propose a hardware implementation of Reed-Solomon (RS) error correction technique for IEEE 802.15.4 wireless sensor network (WSN) based on error pattern analysis. RS error correction code with 32 bytes of error correction capability is chosen for our experimental investigation. Based on the analysis of error pattern, it revealed that there are as much as 81% of burst errors out of the total errors are presented at WSN, and it also shows the rate of occurrence of the burst errors decreases when the burst length increases. Through investigation, the experimental results show the proposed error correction code is able to reduce the packet error rate (PER) significantly for distances shorter than 40 m. At the target PER of 10-3, the proposed technique is able to improve either the transmission distance by about 5 m or the received signal strength indication (RSSI) by about 13 dB. © 2014 IEEE.